Spherical folding tessellations by kites and isosceles triangles IV - Avelino, Catarina P. (Ars mathematica contemporanea, 2016)
The classification of the dihedral folding tessellations of the sphere and the plane whose prototiles are a kite and an equilateral triangle were obtained in C. Avelino and A. Santos, Spherical and planar folding tessellations by kites and equilateral triangles, Australasian Journal of Combinatorics, 53 (2012), 109-125. Recently, this classification was extended to isosceles triangles so that the classification of spherical folding tesselations by kites and isosceles triangles in three cases of adjacency was presented in C. Avelino and A. Santos, Spherical Folding Tessellations by Kites and Isosceles Triangles: a case of adjacency, Mathematical Communications, 19 (2014), 1-28; C. Avelino and A. Santos, Spherical Folding Tessellations by Kites and Isosceles Triangles II, International Journal of Pure and Applied Mathematics, 85 (2013), 45-67; C. Avelino and A. Santos, Spherical Folding Tessellations by Kites and Isosceles Triangles III, submitted. In this paper we finalize this classification presenting all the dihedral folding tessellations of the sphere by kites and isosceles triangles in the remaining three cases of adjacency, that consists of five sporadic isolated tilings. A list containing these tilings including its combinatorial structure is also presented.
Keywords: combinatorial properties; diedrska f-tlakovanja; dihedral f-tilings; kombinatorične lastnosti; sferična trigonometrija; simetrijske grupe; spherical trigonometry; symmetry groups